Comparative Insights into Case Study Methodology in Business Research - Tomasz BOBER (Communications of International Proceedings, 2025)
Case study as a research method is often used in the analysis of best practices in business. Qualitative research to which it belongs is important in the context of benchmarking, but each method has its limitations. The main goal of this article is to systematize knowledge in the field of research methods, with a focus on the case study method. Its purpose is to disseminate existing studies and prepare an outline for the selection of a research method. The characteristic features of the scientific problem are scientific significance, formulating the problem according to rules of conducting the scientific process, as well as taking into consideration limitations and shortage of strict, objective and reliable knowledge. In science, two methodical models are commonly used: the hypothetical-deductive model and the induction model. The hypothetical-deductive model includes a way of presenting scientific explanations in which the truth of the explanation is proved based on the rules of logical reasoning. From general theories, hypotheses are derived, and then they can be studied on the basis of empirical data, using quantitative analysis methods. The inductive model consists in formulating general conclusions or determining the correctness based on the analysis of empirically identified phenomena. Thanks to the comparisons between different research methods, the article clearly describes the possibilities of applying particular techniques in practice, as well as their advantages and limitations. Particular attention was paid to the case study method due to the possibility of its application to the research in the field of economics and management, especially concerning new innovative business solutions, but also due to the fact that research results can be presented subsequently for students as case studies for didactic purposes or can also be used by entrepreneurs, especially by start-ups, to inspect business models that occur in business practice.
Keywords: research method; hypothetical-deductive model; induction model; case study method